Helicobacter pylori infection, premalignant gastric lesions and gastric cancer in the Baltic States: a review - KUPČINSKAS, Limas; MALFERTHEINER, Peter (Acta medica Lituanica, 2011)
Helicobacter pylori (H. pylori) infection has been recognized as a human class I carcinogen in 1994 and linked with the development of gastric cancer in numerous studies. Gastric cancer still ranks as the second leading mortality cause among all cancers in the world and in the fourth place in Europe. High prevalence of H. pylori infection and high incidence of gastric cancer in adults are still characteristic of the Baltic States and resemble patterns in the Western and Northern European countries several decades ago. The recent decline in gastric cancer incidence and mortality as well as H. pylori prevalence in Lithuania, Latvia and Estonia reflects the worldwide trends. H. pylori induced diseases, however, still remain a significant burden for health care systems in the Baltic States. The relevance of H. pylori induced gastric diseases in the Baltic States has stimulated epidemiological, clinical as well as fundamental research on H. pylori infection, premalignant gastric conditions and gastric cancer. This paper reviews original research on H. pylori infection and related diseases in Lithuania, Latvia and Estonia during the period 1992–2011.Keywords: Helicobacter pylori, atrophic gastritis, gastric cancer, Baltic States